Imine‐Induced Metal‐Organic and Covalent Organic Coexisting Framework with Superior Li‐Storage Properties and Activation Mechanism - Zhao, Lu; Tang, Xuxu; Lv, Li‐Ping; Chen, Shuangqiang; Sun, Weiwei; Wang, Yong (ChemSusChem, 2021)
Due to the adjustable structure and the broad application prospects in energy and other fields, the exploration of porous organic materials [metal‐organic polymers (MOPs), covalent organic frameworks (COFs), etc.] has attracted extensive attention. In this work, an imine‐induced metal‐organic and covalent organic coexisting framework (Co−MOP@COF) hybrid was designed based on the combination between the amino units from the organic ligands of Co−MOP and the aldehyde groups from COF. The obtained Co−MOP@COF hybrid with layer‐decorated microsphere morphology exhibited good electrochemical cycling performance (a large reversible capacity of 1020 mAh g−1 after 150 cycles at 100 mA g−1 and a reversible capacity of 396 mAh g−1 at 500 mA g−1) as the anode for Li‐ion batteries. The coexisting framework structure endowed the Co–MOP@COF hybrid with more surface area exposed in the exfoliated COF structure, which provided rapid Li‐ion diffusion, better electrolyte infiltration, and effective activation of functional groups. Therefore, the Co−MOP@COF hybrid material achieved an enhanced Li storage mechanism involving multi‐electron redox reactions, related to the CoII center and organic groups (C=C groups of benzene rings and C=N groups), and furthermore improved electrochemical performance. Two in one: A metal‐organic and covalent organic coexisting framework structure is designed based on the imine‐induced combination between the imine‐based C=N coupled covalent organic framework (COF) and Co‐centered metal‐organic polymer (MOP). The coexisting framework structure retains the exfoliated COF structure with large exposed surface area, along with the resultant multi‐electron redox reaction involving metal centers and organic functional groups in the Co−MOP@COF hybrid electrode for Li‐ion batteries.